Power and principle : human rights programming in international organizations - Oestreich, Joel E. (Advancing human rights series., 2007)
The UN Secretary-General, Kofi Annan, has instructed all UN specialized agencies and other affiliated organizations to consider how their work might advance the cause of human rights around the world. Many of these bodies have taken this call to heart, with a wide range of intergovernmental organizations (IGOs) trying to play a more active role in promoting human welfare. Power and Principle is a comparative study of how and why IGOs integrate human rights standards into their development operations. It focuses on the process of policy innovation in three UN-related IGOs: the UN Children's Fun.